Children praying at Mount Mary Basilica - Mumbai Archive Project Team (Jio Institute, 2024)
Mount Mary Basilica stands as a beacon of faith, hope, and community for Catholic Christians in Mumbai, serving as a cornerstone of their religious and cultural lives.